KETOPROFEN ETHOSOME PERCUTANEOUS PENETRATION TESTING IN IN-VITRO WITH VARIATIONS IN FORM BASE GEL PREPARATIONS - Isriany Ismail; Haeria Haeria; Shabran Hadiq (Jurnal Farmasi UIN Alauddin Makassar, 2015)
It has done research on percutaneous penetration test ethosome ketoprofen in vitro by variations in dosage forms a gel base. This study aims to determine the effect of the type of base gel penetration ability ethosome ketoprofen gel in vitro to produce a good flux. Ethosome ketoprofen gel prepared in dosage forms using two different types of bases, namely using hydrophilic gel base (formula 1) and lipophilic gel base (formula 2). Percutaneous penetration test performed by using Franz diffusion cells with human skin membranes (human cadaver skin) as a diffusion membrane. Ketoprofen assay that penetrate across the skin done for 12 hours. Receptor compartment fluid consisted of phosphate buffer solution pH 7.4, footage was analyzed using UV-Vis spectrophotometer at a wavelength of 308 nm. The test results showed that ketoprofen across the membrane to the formula 1 as 9701.062 μg.cm-2 with 14.10 μg.cm-2.menit-1 speed across the membrane (r=0.995), and the formula 2 as 1209.766 mg.cm-2 with 1,727 μg.cm-2.menit-1 speed across the membrane (r=0.991). Of the two types of base gel is used, it is known that by using a hydrophilic gel base has the ability to penetrate the best drug. It can be concluded that the formulation of ketoprofen gel ethosome can be used transdermally.